Ecdysone and Insulin Signaling Play Essential Roles in Readjusting the Altered Body Size Caused by the dGPAT4 Mutation in Drosophila. - Yan, Y.; Wang, H.; Chen, H.; Lindström-Battle, A.; Jiao, R. (Journal of Genetics and Genomics [Yi chuan xue bao], 2015)
Body size is one of the features that distinguish one species from another in the biological world. Animals have developed mechanisms to control their body size during normal development. However, how animals cope with genetic alterations and/or environmental stresses to develop into normal-sized adults remain poorly understood. The ability of the animals to develop into a normal-sized adult after the challenges of genetic alterations and/or environmental stresses reveals a robustness of body size control. Here we show that the mutation of dGPAT4, a de novo synthase of lysophosphatidic acid, is a genetic alteration that triggers such a robust response of the animals to body size challenges in Drosophila. Loss of dGPAT4 leads to a severe delay of development, slow growth and resultant small-sized animals during the larval stages, but results in normal-sized adult flies. The robust body size adjustment of the dGPAT4 mutant is likely achieved by corresponding changes in ecdysone and insulin signaling, which is also manifested by compromised food intake. Thus, we propose that a strategy has been evolved by the animals to reach final body size when challenged by genetic alterations, which requires the coordinated ecdysone and insulin signaling.